(untitled) (Bangladesh Medical Journal, 2019)
Worldwide intra uterine contraceptive device (IUCD) is a reversible method of contraception. Postpartum IUCD insertion is labeled when IUCD is inserted within 10 minutes to 48 hours of expulsion of placenta. The objective of the study was to analyze the acceptability and feasibility of immediate postpartum intrauterine contraceptive device (PPIUCD) in a tertiary care hospital of Bangladesh. A cross sectional study was conducted among eligible postpartum women at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka Bangladesh. Counseling was done about the procedure of PPIUCD in details. After having the consent, Cu-T 380A was inserted in 343 women. The women were followed up at six weeks after delivery. A total number of 18190 women were counseled during antenatal period and at labor ward. A total number of 6441 were admitted for delivery. Among the admitted patients, 343 accepted this method. Forty nine percent of the acceptors belonged to the age group of 25 – 30 years. Majority were from urban area and had studied up to secondary level. More women from the group who had undergone caesarean section accepted this method than the women who undergone vaginal delivery. Expulsion rate was 1.6% and removal rate 5.8%. Most common reason for removal was irregular per vaginal bleeding. The immediate PPIUCD method appeared to be a safe and effective method of contraception. Bangladesh Med J. 2018 Jan; 47 (3): 25-31